2014
DOI: 10.17576/jsm-2014-4312-08
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Process and Post Mortem Changes: Review

Abstract: Decomposition is degradation process of a corpse into basic respective constituents macroscopically and microscopically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 73 publications
(187 reference statements)
1
12
0
Order By: Relevance
“…The reformed data from day 1 to day 6 is reliable as there were no defects on these readings for 6 consecutive days. Figure 5 shows a positive association between the TBS and the average ambient temperatures from day 1 to day 6, as suggested by previous researchers (Srnka 2003;Teo et al 2014) Moreover, these temperatures are relevant due to the fact that Malaysia is a tropical country where the annual mean temperature is 28°C and will only increase by 0.95°C in every 32 years (Chee-Loong et al 2018). INSECT ACTIVITY Throughout the 10-day observation period, it is found that the presence of ants in a mid-large or large sum could slow down the post-mortem decomposition of a carcass.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The reformed data from day 1 to day 6 is reliable as there were no defects on these readings for 6 consecutive days. Figure 5 shows a positive association between the TBS and the average ambient temperatures from day 1 to day 6, as suggested by previous researchers (Srnka 2003;Teo et al 2014) Moreover, these temperatures are relevant due to the fact that Malaysia is a tropical country where the annual mean temperature is 28°C and will only increase by 0.95°C in every 32 years (Chee-Loong et al 2018). INSECT ACTIVITY Throughout the 10-day observation period, it is found that the presence of ants in a mid-large or large sum could slow down the post-mortem decomposition of a carcass.…”
Section: Discussionsupporting
confidence: 75%
“…The negative correlation coefficient expresses that with an increase in the ambient temperature, there is a decrease in the TBS. The post-mortem decomposition of a carcass or a cadaver speeds up with an increase in ambient temperature (Teo et al 2014). During the current study, the thermocouple malfunctioned on days 0, 7, 8 and 9.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Although these are a convenient means for decomposition stage assessment, they are not always discernible as their supposedly distinctive characteristics usually blend with one another (Pinheiro, 2006;Knobel et al, 2018). Also, decomposition rates vary significantly depending on parameters related to: (i) the environment, such as location, atmospheric conditions and presence of clothing (Voss et al, 2011); (ii) exposure to exogenous organisms such as microbes, insects, plants (Iyengar and Hadi, 2014) and scavenging animals (Behrensmeyer, 1978); (iii) funeral care including embalming, wrapping, type of burial and coffin (Pinheiro, 2006;Tumer et al, 2013;Hau et al, 2014;Lauber et al, 2014); and (iv) cadaver physical condition which includes the circumstances of death, medical treatment, and antemortem and perimortem physical conditions of the deceased (Sutherland et al, 2013).…”
Section: Introductionmentioning
confidence: 99%